NUTRITIONAL CONTENT OF DRY NOODLES SUBSTITUTED WITH CHICKEN LIVER AND RED BEAN FLOUR AS A HIGH-Fe ALTERNATIVE - Sulistyo Febiyanti, Wiwid; Ayu Ainun Nafies, Dian (jfpublisher, 2024)
Introduction. Anemia is a common nutritional problem in developing countries such as Indonesia with a prevalence of 48.9% in adolescent girls who are vulnerable to this condition. Anemia can cause serious health problems. Therefore, additional foods that can increase daily iron intake are needed. One of them is with dry noodles substituted with chicken liver flour and red bean flour. The purpose of this study was to determine the nutritional content of dry noodles substituted with chicken liver flour and red bean flour as a high Fe alternative. Methods. True Experimental Design using a completely randomized design (CRD) with 4 levels of treatment of chicken liver flour substitution and red bean flour, namely P0 (100:0:0), P1 (60:10:30), P2 (60:15:25), P3 (60:20:20). Results&Analysis. The results showed that there was an effect of increasing iron levels in dry noodles. The highest iron content was found in the P3 treatment, which used a substitution of 60% wheat flour, 20% chicken liver flour, and 20% red bean flour, with an iron content of 2.1 mg. Discussion. Dry noodles substituted with chicken liver flour and red bean flour have an effect on increasing iron (Fe) levels. The highest formula is found in formula P3 and the dried noodles have met the quality standards of dried noodles.